Metaphysical Foundations of Alter-Globalization - LEONTYEV, Gleb Dmitrievich; LEONTIEVA, Ludmila Stanislavovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of the study is to substantiate the civilizational prospects and anticrisis worldview potential of alter-globalization based on the determination of its basic and essential characteristics. The study of the globalization process is carried out from the standpoint of a synergistic approach, which allows focusing on the importance of self-organization and the problem of choice. As a result of the analysis, the authors highlight the metaphysical foundations of alter-globalization that determine its historical prospects and increasing effectiveness. These foundations include the principles of freedom, deliberation and self-organization. The specifics of these principles and their practical implementation in the modern context of the potential of a globalizing world are disclosed.RESUMEN El propósito del estudio es corroborar las perspectivas de civilización y el potencial anticrisis de la cosmovisión de la alter-globalización basada en la determinación de sus características básicas y esenciales. El estudio del proceso de globalización se lleva a cabo desde el punto de vista de un enfoque sinérgico, que permite centrarse en la importancia de la auto-organización y el problema de elección. Como resultado del análisis, los autores destacan los fundamentos metafísicos de la alter-globalización que determinan sus perspectivas históricas y su eficacia creciente. Estas bases incluyen los principios de libertad, deliberación y auto-organización. Se revelan los detalles de estos principios y su implementación práctica en el contexto moderno del potencial de un mundo globalizado.